The Influence of Using Animal Card Media on the Ability of Mild Mental Retardatin to Write Simple Sentence - Yunianti, Geas Alida; Efendi, Mohammad; Kurniawan, Agung; Sopingi, Sopingi (Journal of ICSAR, 2019)
This study aims to assess influence the using animal car media on the ability of students with mild mental retardation to write the simple sentence. The study use a qualitative method by an experiment one group pretest-postest design. The data were analized by Wilcoxon signed ranks test. The result show that using animal card media have a significant influence to increasec the ability of students with mild mental retardatio to write the simple sentence.